2014
DOI: 10.3389/fpsyt.2014.00166
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perspectives on Stigma of Mental Illness (an Egyptian Study in a Private Hospital)

Abstract: The present study is concerned with the stigma of mental illness. It examines the subjective element of the experience of stigma among a sample of in-patients with different mental disorders. The sample was taken from consecutive admissions of in-patients meeting International Classification of Diseases, 10th revision (ICD-10) criteria for mental disorders who had capacity to decide on participation in the study and were willing to respond to the structured interview. The study was undertaken in an Egyptian pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Finding hope as reported by service users in this study has been found as an essential factor in promoting recovery from mental health issues in many studies [ 46 , 47 ]. The final theme reported by participants in the current study was clinical recovery; symptoms of mental health issues are disabling and there is high stigma in Egypt [ 48 , 49 ]. Therefore, supporting symptom remission should be supported if an individual express this as a treatment goal.…”
Section: Discussionmentioning
confidence: 99%
“…Finding hope as reported by service users in this study has been found as an essential factor in promoting recovery from mental health issues in many studies [ 46 , 47 ]. The final theme reported by participants in the current study was clinical recovery; symptoms of mental health issues are disabling and there is high stigma in Egypt [ 48 , 49 ]. Therefore, supporting symptom remission should be supported if an individual express this as a treatment goal.…”
Section: Discussionmentioning
confidence: 99%
“…This study, therefore, aims to illuminate how these Nigerian victims of trafficking experience(d) stigma and sexual stigma during their trajectories, and how they perceive, interpret, and are impacted by those experiences of stigma. This study adds to the limited literature on the narratives of victims of stigma (Sidhom et al, 2014), sexual stigma (Dahal et al, 2015), and Nigerian victims of trafficking (Esposito et al, 2016; Tessitore & Margherita, 2022) who must deal with the lasting consequences of sexual violence while navigating the negative individual and societal perspectives, judgements, and labels (Adeyinka et al, 2023). The central intersectional approach which includes the participants’ identities as female and Black adds complex and integrated layers to their experiences with the understanding that “social positions intersect at the individual level (e.g., race and gender)” (Bauer et al, 2021, p. 2).…”
Section: Human Trafficking Stigma and Labeling Of Nigerian Victimsmentioning
confidence: 99%
“…72 Another study found that patients' experience of stigma is rarely related to the name of the diagnosis. 73 A study that examined changing the name of schizophrenia due to its stigma did not yield significant differences. 74 We could not find studies on the impact of changing the name of ECT.…”
Section: Effective Ways Of Managing Stigmamentioning
confidence: 99%